First aid literacy mobile application development - Pattaraporn Khuwuthyakorn (2018)
© 2018 Association for Computing Machinery. First aid treatment in medical emergencies is very important especially in serious injuries, which can increase the survival of emergent patients and reduce risk of permanent disability. The primary first aid procedures provide practical guidelines of the initial care to a person suffering an injury or illness by following the standard method of first aid before secondary care. Nowadays, mobile phone could be a useful tool to provide essential information and a quick reference in first aid. The research questions are how appropriate design of an application should be to suit a first aid leaning tool? What necessary functions for someone to deal with any unexpected situations or accidents should be? The purpose of this study is to develop the First Aid Literacy Mobile Application (FALMA) by using the rapid prototyping methodology together with the Ionic framework. The application has been designed by considering necessary functions such as location service and first aid treatment information. The result of the development and testing are discussed.